Antibiogram resistance pattern of extended-spectrum beta-lactamase-positive bacterial isolates - Manjunath, B S; Adarsh, E; Rajanish, K V; Trupthi, S; Niveditha, C; Raj, Darshan K (Indian Journal of Child Health, 2017)
Objectives: To identify the antibiogram resistance pattern of extended-spectrum beta-lactamase (ESBL)-positive bacterial isolates. Materials and Methods: This prospective, observational study was conducted in Rajarajeswari Medical College and Hospital, Bangalore, over a period of 12 months. The clinical samples were inoculated on the standard recommended media. Inoculated plates were incubated aerobically at 37°C for 24 h, and organisms were identified by culture and appropriate biochemical reactions. Antimicrobial sensitivity was performed by Kirby-Bauer disk diffusion method on Mueller-Hinton agar using commercially available antibiotic discs as per the Clinical and Laboratory Standards Institute Guidelines-2014. Results: Escherichia coli were the most common ESBL-producing organisms isolated from the study population accounting to 45% of the total cases. The next most common organisms were Klebsiella species and Pseudomonas. Ceftriaxone was the most commonly used empirical antibiotic (33.3% cases). Piperacillin and meropenem were used in combination with tazobactam or sulbactam, respectively, as per the culture and sensitivity reports. Conclusion: The association of change in antibiotic to mortality was found to have significance. The change in antibiotic in deterioration of the illness showed decrease in mortality.